On the boundary conditions in multi-phase flow through the piston ring-cylinder liner conjunction. (October 2015) - Shahmohamadi, H.; Mohammadpour, M.; Rahmani, R.; Rahnejat, H.; Garner, C.P.; Howell-Smith, S.
Abstract: Prediction of load capacity and friction depends on the assumed boundary conditions. The inlet comprises swirl and counter flows, admitting only a portion of the inward flow into the conjunctional gap. At the contact exit, the lubricant film ruptures with multi-phase flow through a cavitation region. Therefore, the boundary conditions affect the load carrying capacity and friction. A Navier–Stokes solution of multi-phase flow, including vapour transport is presented, with determined realistic boundary conditions. The evaluated boundaries agree with potential flow analysis satisfying compatibility conditions, not hitherto reported in literature. The investigation is extended to the determination of optimum compression ring contacting geometry. Highlights: CFD model of piston ring conjunction, including vapour transport is presented. Model takes into account counter and swirl flows at the inlet. Stagnation boundary is determined. Influence of cavitation is included by modified Rayleigh–Plesset. The model demonstrates the importance of realistic boundary conditions.